Integrative transcriptomics analysis reveals the metabolic regulatory functions of lncRNA in the livers of yak at different age stages - Hongsen Fu; Wei Xia; Fang Fu; Jun Yi; Wei Wang; Yong Wei; Li Wang (PLoS ONE, 2025)
Exploring the regulatory role of long non-coding RNA (lncRNA) in plateau yak is crucial to understanding its metabolic network for adapting to extreme environments. By integrating transcriptomic sequencing and co-expression network analysis, the messenger RNA (mRNA) and lncRNA expression characteristics of yak liver at three growth and development stages were systematically analyzed. A total of 35,216 mRNAs and 10,073 lncRNAs were detected. Among the 288 differentially expressed lncRNAs, 88 lncRNAs related to metabolism were screened, and their potential functions in lipid metabolism, collagen remodeling, and protein transport were predicted. The age-dependent expression patterns of some lncRNAs were verified through qRT-PCR (quantitative real-time reverse transcription polymerase chain reaction) experiments, which initially revealed the status and role of lncRNAs in metabolic regulation in yak liver. This study provides new insights into the molecular mechanisms underlying metabolic adaptation in high-altitude species such as yak, and establishes a methodological framework for the screening and identification of functional lncRNAs in non-model organisms.